Editorial: Regulation and Convergence - Campbell, Leith H (Journal of Telecommunications and the Digital Economy, 2023)
This editorial argues from content in this issue that telecommunications regulation has not kept pace with convergence of telecommunications and content providers. It suggests that the loose co-ordination between regulations and regulators for telecommunications services and digital platforms no longer makes technological sense within the converged architectures of 5G and 6G.In addition, all the published papers, not just those relating to regulation, are briefly described. This issue also includes an obituary for John Burke, an influential member of this Journal’s Editorial Advisory Board.